Fully Understanding Concept Possession - Víctor M. Verdejo (Crítica)
Can subjects genuinely possess concepts they do not understand fully? A simple argument can show that, on the assumption that possession conditions are taken to fully individuate concepts, this question must be answered in the negative. In this paper, I examine this negative answer as possibly articulated within Christopher Peacocke’s seminal theory. I then discuss four central lines of attack to the view that possession of concepts requires full understanding. I conclude that theorists should acknowledge the existence of indefinitely many cases of genuine concept possession for partially understood concepts and therefore face the determination challenge, namely, the challenge of fully determining concept individuation from concept possession conditions of partially understood concepts.